Verliert das Hörbuch seinen Körper? Die Auswirkungen des Downloads auf Bibliotheken, Buchbranche und Nutzer. Begleitband zur gleichnamigen Tagung - Rühr, Sandra (2010)
The present volume is the companion volume to a conference of the same name. Six experts from libraries, the book industry and science gave lectures on the digitalization and de-materialization in the audiobook sector. At first, the volume Verliert das Hörbuch seinen Körper (Is the audiobook losing its body?) pursues the audiobook’s development in general. Downloading audiobooks has been an alternative to physical forms of the audiobook since 2004 and is fit to expand both content-related range and the target group. From a publishing point of view this assumption is qualified. From a library-oriented point of view the importance of the medial from audiobook in public libraries and the experiences with “non-corporeal” products within library-oriented daily life.
BUCHWISS::pub-39